Synthesis of a Polyanion Cathode Material, Li[sub 2]Co[sub 2](MoO[sub 4])[sub 3], and Its Electrochemical Properties for Lithium Batteries - Prabaharan, S. R. S.; Michael, M. S.; Begam, K. M. (2004)
High voltage redox properties of a polyanion material, Li2Co2(MoO4)(3), as positive electrode was demonstrated against lithium for the first time. The orthorhombic structure showed reversible extraction and insertion cycles of lithium at a potential of ca. 4.9 V vs. Li+/Li as well as 1.5 V. The former potential was attributed to Co2+/Co3+ and the latter to Mo6+/Mo5+. The reason for the change in charge/discharge curves after the first charge is clearly demonstrated by the structural changes (monoclinic, P2/m) caused by electrochemical extraction and insertion of lithium as deduced from the ex situ X-ray diffraction analysis on the cycled electrode pellet. (C) 2004 The Electrochemical Society.